Bridging the Gap: A Case Study on How NGOs and International Organizations Expand Access to Early Childhood Education in Afghanistan - Basira Mujadidi; Hazrat Shah Kayen (SEA-CECCEP, 2025)
Early Childhood Care and Education (ECCE) is known worldwide as an important foundation for children’s lifelong learning and development. The paper will discuss how non-governmental organizations (NGOs) and other international agencies can improve the accessibility to ECCE in Afghanistan, what challenges they face and whether their programs are sustainable. The qualitative case study design was used, including semi-structured interviews with the employees of the NGO and the analysis of documents, such as the reports and policy materials. Thematic analysis has demonstrated that there are some recurrent themes, which are capacity building, community-based strategies, teacher training, inclusion, and sustainability. The findings suggest that NGOs have stopped their supportive roles in ECCE to take up the dominant roles in the delivery of education, which involves integrated education, health, and social participation. However, the barriers are the insufficiency of funds, gender limitation, and unpredictable policies. Findings are minimal and cannot be generalized to other weak environments. The limitations are the limited sample size and inaccessibility to organizations that may influence the field of views elicited. The paper concludes that sustainable ECCE with regard to fragility requires long-term investment, ownership of the communities, and policy coherence.